EFFECT OF PASSIVE MODIFIED ATMOSPHERE PACKAGING AND PRETREATMENT ON POST HARVEST QUALITY OF GREEN PIGEON PEA KERNELS STORED UNDER AMBIENT CONDITION - PRADIP A. BORKAR,; AKSHAY R. MALI,; AMIT R. DORKAR,; ASHWINI M. CHARPE,; MAHENDRA R. RAJPUT,; RAJESH P. MURUMKAR, (The Bioscan, 2021)
Green pigeon pea kernels (GPPK’s) are protein rich vegetable. GPPK of BDN-2001-2009 at 70 days of crop maturity was tested to improve shelf-life and reduced browning. 17 treatments of blanching temperature 75, 85, 95°C in combination with 1, 4, 7 min treatment duration and two packaging films polypropylene (PP) and low density polyethylene (LDPE) of 100, 200, 300 gauge were applied. Packets were stored at ambient condition (15- 38°C; 19-49% RH). Observations were recorded at 4 days interval till 12 th day for physiological loss of weight (PLW), firmness, color deviation, moisture content and sensory status. Experiment was conducted in Box- Behnken model and 17 treatments with 6 categoric factors giving 102 treatment combinations were studied. Optimized independent parameters for modified atmosphere packaging of GPPK by response surface methodology were 93.73°C blanching temperature, 1 min blanching time and 267.64 gauge packets. Predicted responses were 0.87% PLW, 3.83 N firmness, 47.83% color deviation, 61.46% moisture content and sensory status of 8.83. Blanching for 1 min at 95°C and packaging in 300 gauges PP, nearest to optimized treatment was found acceptable by HACCP standards at level-2 for microbial load with headspace composition of 12.9% O 2 and 8.1% CO 2 on 12 th day under ambient storage.